Pesticides exposure and cardiovascular hemodynamic parameters among male workers involved in mosquito control in East Coast of Malaysia - Samsuddin, Niza; Rampal, Krishna Gopal; Ismail, Noor Hassim; Abdullah, Nor Zamzila; Nasreen, Hashima E (Oxford University Press, 2015)
BACKGROUND Research findings have linked exposure to pesticides to an increased risk of cardiovascular (CVS) diseases. Therefore, this study aimed to assess the impact of chronic mix-pesticides exposure on CVS hemodynamic parameters.